STRATEGI PEMERINTAH DALAM MENANGANI TINDAK KEKERASAN PADA ANAK DI KOTA BANDAR LAMPUNG - Gustiany, Shinta Dwi; Nora, Endah; Ernanda, Erdin Auriski (Ensiklopedia of Journal, 2024)
Seeing the phenomenon of many cases of violence against children in Bandar Lampung City, the Bandar Lampung City Women's Empowerment and Child Protection Service made several regulations related to child protection. The PP & PA Department of Bandar Lampung City as a public organization needs a strategy to achieve the goals that have been set. If the strategy implemented is right on target then everything will run smoothly, and vice versa. This research uses strategic management theory. The indicators of strategic management are environmental observation, strategy formulation and strategy implementation. This type of research uses field research which is qualitative descriptive research. By using the new institutionalism or new institutional approach. The data collection technique for this research is observation, interviews and documentation.The results of the research show that in the strategic management of the Bandar Lampung City PP & PA Service, based on indicators, environmental observations of the Bandar Lampung City PP & PA Service have carried out environmental observations in understanding organizational opportunities and threats. Furthermore, in formulating strategies, the Bandar Lampung City PP & PA department supports and strives to make the city of Bandar Lampung a child-friendly regional city. Then implementing the strategy, the PP & PA Department of Bandar Lampung City has a program that has been implemented quite well and on target. Not only that, in advocacy for prevention efforts carried out by the PP & PA Department of Bandar Lampung City, it has also collaborated with institutions operating in the same field in socializing the prevention of violence and fulfillment of children's rights in Bandar Lampung City.Keywords: Strategy, Public Policy, PP & PA Department